Optimalisasi Penggunaan Teknologi Dalam Implementasi Kurikulum Di Sekolah (Persepektif Teori Konstruktivisme) - I Ketut Sudarsana (Cetta: Jurnal Ilmu Pendidikan, 2018)
Science and technology are constantly evolving, demanding all the potential of human ability to be self-actualizing. Implementation of curriculum in schools, especially in the structure of education aims to educate students for ethics and good morals. The phenomenon that occurs in the field shows every get a lesson of Hindu religious education students often feel bored and consider the education of Hinduism is not important, therefore need to be pursued a learning activity that is able to provide conditions to students to develop the ability to think optimally one way is to apply the activities learning in accordance with the Curriculum 2013.